2019
DOI: 10.3310/hta23150
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab in combination with methotrexate for refractory uveitis associated with juvenile idiopathic arthritis: a RCT

Abstract: Background Children with juvenile idiopathic arthritis (JIA) are at risk of uveitis. The role of adalimumab (Humira®; AbbVie Inc., Ludwigshafen, Germany) in the management of uveitis in children needs to be determined. Objective To compare the efficacy, safety and cost-effectiveness of adalimumab in combination with methotrexate (MTX) versus placebo with MTX alone, with regard to controlling disease activity in refractory uve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…of participants, F/M) Control group (no. of participants, F/M) Age, years Length of follow-up (months) Control of intraocular inflammation (TG vs CG) Visual acuity Corticosteroid sparing (TG vs CG) AEs and SAEs (TG vs CG) Ramanan, et al [ 27 ] (EudraCT number, 2010–021,141-41) RCT, DB 90 ADA (60, 47/13) 20 mg/0.8 ml for participants weighing < 30 kg or 40 mg/0.8 ml for participants weighing ≥ 30 kg Placebo (30, 23/7) 8.9 18 Number of participants failing treatment (14/60 vs 17/30) (RR 0.40, 95% CI 0.23–0.72; P = 0.002) NA 4/7vs2/2 AEs 59 vs 26 The rate of AEs (10.60 per PY, 95% CI 9.77–11.44 per PY)vs (7.12 per PY, 95% CI 5.89–8.53 per PY) SAEs 13 vs 2 The rate of SAEs (0.29 per PY vs 0.19 per PY) Quartier et al [ 28 ] (Trial registration number: NCT01385826) RCT, DB 31 ADA (16, 15/1) 24 mg/m 2 in patients aged < 13 years, 40 mg in the others, every other week Placebo (15, 13/2) 9.5 (4.9–29.1) 12 30% reduction of Inflammation on LFP: 9/16 vs 3/15 (P = 0.038, χ 2 test; RR = 2.81, 95% CI 0.94–8.45; RD = 36.3%, 95% CI 2.1–60.6); logMAR: 0.1 (− 0.2 to 1.3) to 0.15 (− 0.10 to 1.10) NA NA Janine A. Smith et al [ 29 ] (Trial registration number: NCT00012506) RCT, DB 12 ETA (7, 4/3) 0.4 mg/kg to a maximum of 25 mg subcutaneously twice weekly for 6 months Placebo (5, 5/0) 11 (6–15) 6 AC cells to 0 or topical corticosteroid < 3 times/day or 50% reduction in number or dose of other anti-inflammatory medications: 3 (95% CI 0.10–0.82) vs 2 (95% CI 0.05–0.85) ( P = 1.0) NA 0/2vs0/2 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…of participants, F/M) Control group (no. of participants, F/M) Age, years Length of follow-up (months) Control of intraocular inflammation (TG vs CG) Visual acuity Corticosteroid sparing (TG vs CG) AEs and SAEs (TG vs CG) Ramanan, et al [ 27 ] (EudraCT number, 2010–021,141-41) RCT, DB 90 ADA (60, 47/13) 20 mg/0.8 ml for participants weighing < 30 kg or 40 mg/0.8 ml for participants weighing ≥ 30 kg Placebo (30, 23/7) 8.9 18 Number of participants failing treatment (14/60 vs 17/30) (RR 0.40, 95% CI 0.23–0.72; P = 0.002) NA 4/7vs2/2 AEs 59 vs 26 The rate of AEs (10.60 per PY, 95% CI 9.77–11.44 per PY)vs (7.12 per PY, 95% CI 5.89–8.53 per PY) SAEs 13 vs 2 The rate of SAEs (0.29 per PY vs 0.19 per PY) Quartier et al [ 28 ] (Trial registration number: NCT01385826) RCT, DB 31 ADA (16, 15/1) 24 mg/m 2 in patients aged < 13 years, 40 mg in the others, every other week Placebo (15, 13/2) 9.5 (4.9–29.1) 12 30% reduction of Inflammation on LFP: 9/16 vs 3/15 (P = 0.038, χ 2 test; RR = 2.81, 95% CI 0.94–8.45; RD = 36.3%, 95% CI 2.1–60.6); logMAR: 0.1 (− 0.2 to 1.3) to 0.15 (− 0.10 to 1.10) NA NA Janine A. Smith et al [ 29 ] (Trial registration number: NCT00012506) RCT, DB 12 ETA (7, 4/3) 0.4 mg/kg to a maximum of 25 mg subcutaneously twice weekly for 6 months Placebo (5, 5/0) 11 (6–15) 6 AC cells to 0 or topical corticosteroid < 3 times/day or 50% reduction in number or dose of other anti-inflammatory medications: 3 (95% CI 0.10–0.82) vs 2 (95% CI 0.05–0.85) ( P = 1.0) NA 0/2vs0/2 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding three RCTs, a study conducted by Ramanan et al [ 27 ] had a low risk of bias in all items. The other two studies [ 28 , 29 ] had an unclear risk of bias in allocation concealment and blinding of outcome assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two RCTs (trials SYCAMORE and ADJUVITE) confirmed clinical efficacy of anti-TNF- α antibody for uveitis associated with juvenile idiopathic arthritis (JIA) [ 15 , 20 ], and they were also included in this study. Meta-analysis illustrated that compared with placebo or other drugs, immunosuppressant therapy for noninfectious uveitis had clinical efficacy to some extent, whereas there was moderate heterogeneity among studies.…”
Section: Discussionmentioning
confidence: 99%